An Econometric Study of the Development of the Volume of Foreign Trade in Syria During the Period 2000-2019 - دالي علي; راميا الجبيلي; محمد معد سليمان (Latakia University Journal - Economic and Legal Sciences Series, 2023)
The research aimed to study the development of the volume of foreign trade in Syria during the period 2000-2019. The research relied on the analytical descriptive approach by describing and analyzing foreign trade indicators during the period studied, based on the statistical collections issued by the Central Bureau of Statistics. Eviews.10 was used, where an ARIMA model was estimated according to the Box-Jenkins methodology, and the results showed that the development of foreign trade exports and imports was almost linear, and for exports it was concluded that the ARIMA (2,0,0) model is the best, based on According to several statistical standards, and for imports, the ARIMA (1,0,0) model was the best, as it showed an increase in foreign trade data until 2009 and a decrease after this period due to the restriction of global trade after 2008 and the entry into the war period on Syria after 2011 Affected by the package of Arab, European and American sanctions, which restricted exports, while the linear development continued with regard to imports, especially after 2011, due to the disruption of production in a large number of sectors.